(untitled) (Journal of Accessibility and Design for All, 2019)
This paper examines the barriers concerning access to hotel facilities in India, which leads to the physical exclusion of tourists with some form of physical disability. This research aims to analyse the existing facilities available in a hotel as experienced by these users with regard to mobility, circulation, and access to services in all categories of hotels in India. People with disabilities (PwD) have the same motivation to travel and experience tourism as other tourists but are impeded owing to the challenges that they experience in hotels. This study focuses on PwD’s perspectives on the concept regarding barrier-free hotel design and planning in India, which encourages ‘accessible tourism’. Furthermore, this research employs a quantitative analysis from the users’ perspective pertaining to differently abled tourists with respect to the concepts of ‘barrier-free’ and ‘accessible tourism’. The users’ experiences have been rated for hotels ranging from budget to 5-star categories. Moreover, the research findings indicate that although barrier-free tourism is emerging as a concept in India, many hotels are yet to implement universal standards concerning accessibility. While the Ministry of Tourism, Government of India, has taken several initiatives to provide barrier-free tourism in 4- and 5-star hotels to make their facilities accessible for PwD, this research recommends that such facilities should be upgraded in budget hotels as well, in order to develop affordable and inclusive hotel design. In addition, this study emphasizes the relevance of universal design and proposes a new paradigm to establish inclusive hotels, which can further encourage domestic and international tourists to experience the rich culture and heritage of India.